The choice of means and methods treatments of permanent teeth - Луцкая, И. К. (Actual Dentistry, 2019)
Summary. In article the analysis of use of the photocured composition materials in concrete clinical situations is provided. Indications to the choice of means and methods of treatment of defects of solid tissues of tooth depend on age of the patient, symptoms of manifestation of pathological process, its depth and Summary. In article the analysis of use of the photocured composition materials in concrete clinical situations is provided. Indications to the choice of means and methods of treatment of defects of solid tissues of tooth depend on age of the patient, symptoms of manifestation of pathological process, its depth and prevalence. Recommendations about the differentiated use of modern dental materials when modeling esthetic designs are provided. Key words: photocomposite, caries, treatment, esthetic restoration.